Pengaruh Corporate Social Responsibility dan Persistensi Laba terhadap Earnings Response Coefficient - Izzah Hakimatul Aliyah Addini; Suwarno Suwarno (Akuntansi, 2024)
This research aims to examine the influence of Corporate Social Responsibility and Profit Persistence on the Earnings Response Coefficient. The data sources used in this research are property and real estate sector companies using documentary data obtained from the official website of the Indonesian Stock Exchange. The sample used in this research was 60 data from property and real estate companies in 2021-2022 using purposive sampling. This research uses multiple linear regression analysis techniques. The regression results show that Corporate Social Responsibility has a positive effect on the Earnings Response Coefficient, earnings persistence has no effect on the Earnings Response Coefficient.